1982
DOI: 10.1159/000115447
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical Lesions of the Brachial Plexus

Abstract: 34 subjects with 36 obstetrical paralysis of the brachial plexus were studied. The diagnosis was made immediately after birth in the great majority. 5 pareses of the lower plexus, however, were only recognized later. All subjects were first seen by us under the age of 13 years, 25 during the first year of life. At follow-up the age of the 34 subjects varied between 3 and 24 years. 32 patients had undergone daily physiotherapy, in 5 electrotherapy had also been applied. There was no correlation between these tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…They postulated that orthograde trans-synaptic degeneration of the postganglionic neuron had taken place. Although the association of Klumpke’s paralysis is well recognised,16this was not present in any of our patients.…”
Section: Discussioncontrasting
confidence: 51%
“…They postulated that orthograde trans-synaptic degeneration of the postganglionic neuron had taken place. Although the association of Klumpke’s paralysis is well recognised,16this was not present in any of our patients.…”
Section: Discussioncontrasting
confidence: 51%
“…The high frequency of difficult deliveries with associated injuries in this series, similar to the experience of other workers, suggests that traction and compression of the nerves were responsible for the lesions in our cases, rather than local injury to the shoulder and humerus. 4,8,[12][13][14] The late presentation to the hospital in the majority of our cases probably reflects the relatively good prognosis of the disease, as complete recovery is encountered in 70% to 92% of cases. 10,11,15 The proportion of the cases who reported late to the hospital most likely represents the group with more severe lesions, and as such, they have a poorer prognosis…”
Section: Discussionmentioning
confidence: 99%
“…While the definition of recovery has not been made clear, it has been stated that 80-90% complete neural recovery has been seen, according to studies. Meanwhile, other studies have found complete recovery in less that (approximately) 50% of cases [8][9][10][11]. Nervous recovery is not always accompanied by functional recovery, and sequelae, such as joint contractures and subluxations, may remain in some patients [12].…”
Section: Introductionmentioning
confidence: 99%